2019
DOI: 10.1371/journal.pone.0215890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pressure pain thresholds in collisions with collaborative robots

Abstract: In recent years, safety issues surrounding robots have increased in importance, as more robots are in close contact with humans, both in industrial fields and elsewhere. Safety standards for industrial robots operating in specific spaces have been established, but no such standards have been specified for collaborative and service robots. To establish safety standards for such robots, we assessed pressure pain thresholds for collisions between humans and robots, under the assumption that the pain threshold is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…In our study the ME/CFS patients without FM had a similar baseline PPT on the finger compared to HC, and a lower baseline PPT on the shoulder compared to HC. A recent study in HC by Park et al showed higher PPT on hands and fingers compared to the PPT of muscular parts, indicating the finger to be relatively less sensitive to pain (41). Despite the absence of a difference in PPT of the finger in patients without FM, PPT of the shoulder were significantly lower than that of HC.…”
Section: Discussionmentioning
confidence: 87%
“…In our study the ME/CFS patients without FM had a similar baseline PPT on the finger compared to HC, and a lower baseline PPT on the shoulder compared to HC. A recent study in HC by Park et al showed higher PPT on hands and fingers compared to the PPT of muscular parts, indicating the finger to be relatively less sensitive to pain (41). Despite the absence of a difference in PPT of the finger in patients without FM, PPT of the shoulder were significantly lower than that of HC.…”
Section: Discussionmentioning
confidence: 87%
“…Then, the subject was placed in the testing system and the body part was secured. To be consistent with the procedure followed by Melia et al (2019) and Park et al (2019), the subject was reminded to stop the load test the moment the pressure felt at the body location changed to a slight painful feeling. In each subject's first session, several test runs were executed to familiarize them with the procedure and to train their ability to distinguish the pain from discomfort.…”
Section: Work Plan and Proceduresmentioning
confidence: 99%
“…Unlike other studies with a similar scope, Melia et al focused on limits based on peak pressures, instead of maximum forces. Park et al (2019) repeated their experiments with 90 male subjects, but only on 15 body locations.…”
mentioning
confidence: 99%
“…Different metrics have been offered to estimate and quantify injuries deriving from human-robot collisions [14][15][16][17][18]. These works cover industrial robots and define clear criteria to minimize injuries that impact the robot's shape, weight, velocity, and direction in which it may approach humans.…”
Section: Measures Of Risks Inherent To Collisions With Robotsmentioning
confidence: 99%